2022
DOI: 10.5114/fpn.2022.123246
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of the central nervous system injury in Wilson’s disease

Abstract: symptoms of WD are mainly symptoms of liver damage (from a mild increase in the activity of liver enzymes to liver failure) and the central nervous system (CNS) (mainly a wide spectrum of involuntary movements). The article aims to review currently proposed biomarkers of CNS damage in WD: 1) clinical; 2) structural (neuroimaging) and 3) molecular, including a proposal of their future role (prognostic, diagnostic or monitoring of response to treatment). Literature review. WD is one of the few metabolic diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…A study of a large cohort of WD patients confirmed there was a gender effect in index patients: Hepatic presentation was more common in females, and neurologic presentation was more common in males (Ferenci et al, 2019). Agnieszka et al conducted a higher sNFL concentration (a marker of neurodegeneration) was observed in men (estrogens are thought to have a neuroprotective effect in neurodegenerative diseases) (Antos et al, 2022). In our study, compared to females, males had thinner partial perifovea zones in inner retina layer.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…A study of a large cohort of WD patients confirmed there was a gender effect in index patients: Hepatic presentation was more common in females, and neurologic presentation was more common in males (Ferenci et al, 2019). Agnieszka et al conducted a higher sNFL concentration (a marker of neurodegeneration) was observed in men (estrogens are thought to have a neuroprotective effect in neurodegenerative diseases) (Antos et al, 2022). In our study, compared to females, males had thinner partial perifovea zones in inner retina layer.…”
Section: Discussionsupporting
confidence: 68%
“…Agnieszka et al. conducted a higher sNFL concentration (a marker of neurodegeneration) was observed in men (estrogens are thought to have a neuroprotective effect in neurodegenerative diseases) (Antos et al., 2022). In our study, compared to females, males had thinner partial perifovea zones in inner retina layer.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological impairment is the most important clinical manifestation of WD disease, accounting for over 50% of the total cases (Dusek et al., 2019; Litwin et al., 2019). Anti‐copper treatment for WD requires treatment monitoring of patients to prevent serious adverse events, especially early neurological deterioration (Antos et al., 2023). The monitoring and evaluation of neurological symptoms using the Unified Wilson's Disease Rating Scale or the Global Assessment Scale for WD, as well as quantitative monitoring of blood biomarkers for central nervous system injury in WD (such as neurofilament proteins, glial fiber acid protein, tau proteins, and ubiquitin carboxyl terminal hydrolase L1), are effective methods for preventing early neurological deterioration (Ziemssen et al., 2022, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…It hydrolyses small C-terminal adducts of ubiquitin to produce ubiquitin monomer, which is needed for axonal stability. UCH-L1 expression is mostly seen on neurons, cells of the neuroendocrine system, testes, and ovaries [17,23,31,32]. Mutations in UCH-L1 gene are described in the etiology of PD and AD as causing disturbances with other proteins involved in neurodegenerative disorders (parkin and alfa synuclein) [23].…”
Section: Ubiquitin Carboxyl-terminal Hydrolase L1mentioning
confidence: 99%
“…Additionally, structural assessments are performed, such as using a brain magnetic resonance imaging (MRI) semiquantitative scale to assess acute toxicity or chronic damage, [15,16] or using ultrasound examination, computed tomography (CT), MRI with or without elastography, and fibroscan for liver fibrosis assessment [1,8,15,16]. In addition, there is a need to find quantitative and objective diagnostic and therapeutic blood-based biomarkers of central nervous system (CNS) injury to: (1) facilitate treatment monitoring; (2) identify patients who are at risk of neurological deterioration; and (3) aid in the investigation of disease progression, especially neurological disease progression, to observe the natural course of disease [11,12,[15][16][17]. The aim of this review is to provide an overview of serum biomarkers of CNS injury that have been assessed in WD.…”
Section: Introductionmentioning
confidence: 99%